005 Non-invasive stress imaging as a gatekeeper to complete revascularisation in stemi patients with moderate bystander disease at primary percutaneous coronary intervention. (5th May 2016) - Dastidar, Amardeep Ghosh; Nightingale, Angus K; Johnson, Thomas W; Rodrigues, Jonathan CL; Carpenter, Alexander; Cengarle, Marco; Baritussio, Anna; McAlindon, Elisa; Augustine, Daniel X; Angelini, Gianni; Strange, Julian; Baumbach, Andreas; et al.
Abstract : Introduction: 40% of patients presenting with STEMI have multivessel disease (MVD). Current international guidelines recommend revascularisation of the culprit artery only. However recent trials (PRAMI/CVLPRIT) have shown a superiority of complete in-hospital revascularisation. Objective: Assess the role of non-invasive stress imaging as a gatekeeper to complete revascularisation in STEMI patients with moderate bystander disease. Methods: A registry study of consecutive patients who underwent Primary Percutaneous Coronary Intervention (P-PCI) of the culprit artery. Significant MVD was defined as non-culprit stenosis ≥50% in large proximal epicardial vessel, or ≥75% elsewhere (moderate if 50–74% stenosis in large proximal epicardial vessel, or 75–94% elsewhere). Non-invasive stress imaging was performed at 4 weeks. Patients with severe or critical bystander disease were excluded from the study. A simple cost analysis model was built for UK and USA. Results: 1, 167 patients were included (74% males, 64 years), 33% demonstrating MVD. 40% of MVD underwent stress CMR, and 36% a stress echocardiogram. The remaining 93 patients underwent direct revascularisation or were lost to follow up. Only 47% had evidence of inducible myocardial ischaemia in moderate bystander coronary artery disease (61/157 in stress CMR and 78/141 in stress echocardiogram). When PCI in MVD is performed only in the presence of inducible myocardial ischemia, there is saving. (UK or US). Conclusions: <50% patients with moderate MVD at PPCI have inducible myocardial ischemia in the moderate bystander disease. Non-invasive stress imaging as a gatekeeper to complete revascularisation, may potentially reduce the number of PCIs, also resulting in a cheaper management strategy.